Misclassification of physical work exposures as a design issue for musculoskeletal intervention studies - Gardner, L. I.; Landsittel, D. P.; Nelson, Nancy A.; Pan, C. S. (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study determined the impact of misclassification due to using job titles as surrogate variables for physical work exposures to assess confounding in a study of the preventive effect of back belts on back injury. The authors present retail merchandise data that quantify misclassification from residual confounding by physical work exposures on injury rate ratios when available administrative job titles are used.' ' METHODS ': 'Job title and direct observation data on 134 workers were used to calculate the percentage to which the job-title-adjusted rate ratio for back injury accounts for confounding by the true physical work exposures, awkward postures, and heavy weight handling. Workers' compensation data, an estimate of the effect of back belts from the literature and the percentage of adjustment of the rate ratio due to the job title variable were used to calculate the magnitude of bias from the rate ratio adjusted for job title.' ' RESULTS ': 'The job title variable was found to have sensitivities of 97% and 85% and specificities of 68% and 58% for awkward postures and heavy weight handling, respectively. The magnitude of confounding bias remaining for the back-injury rate ratio when the job title surrogate was used was 24% for postures and 45% for heavy weight handling.' ' CONCLUSIONS ': 'The administrative job title performed poorly in this setting; residual confounding was sufficient to bias the rate ratio from 2.0 to 1.3. The effect of additional sources of misclassification and the need for better exposure measures than job title are discussed.
Keywords: back injury; misclassification; residual confounding; work-related musculoskeletal disorder